Potential and Prospects for Regional Energy Trade in the South Asia Region - World Bank (Washington, DC, 2014)
South Asian region is enjoying unprecedented economic growth. The growth, however, is becoming constrained by significant shortages in energy supply, and unless corrective steps are urgently initiated and implemented, it may be difficult to sustain the achieved growth rates. The region's political leaders and its business community are increasingly recognizing the need to foster cross-border energy investments and promote regional energy trade in order to take full advantage of the energy resources available within the region. This study describes the potential and identifies the main opportunities for development of regional trade in electricity and gas. The study also identifies the policies that the governments should pursue to promote cross-border energy trade and describes the supporting role of the international financing institutions. The author hope that the study will stimulate further interest and contribute to development of energy trade within South Asia Region and between the region and its neighbors.